Bismuth Phosphinates in Bi‐Nanocellulose Composites and their Efficacy towards Multi‐Drug Resistant Bacteria. Issue 49 (27th July 2018) - Werrett, Melissa V.; Herdman, Megan E.; Brammananth, Rajini; Garusinghe, Uthpala; Batchelor, Warren; Crellin, Paul K.; Coppel, Ross L.; Andrews, Philip C.
Abstract: A series of poorly soluble phenyl bis ‐phosphinato bismuth(III) complexes [BiPh(OP(=O)R 1 R 2 )2 ] (R 1 =R 2 =Ph; R 1 =R 2 = p ‐OMePh; R 1 =R 2 = m ‐NO2 Ph; R 1 =Ph, R 2 =H; R 1 =R 2 =Me) have been synthesised and characterised, and shown to have effective antibacterial activity against Escherichia coli ( E. coli ), Staphylococcus aureus ( S. aureus ), methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococcus (VRE). The bismuth complexes were incorporated into microfibrillated (nano‐) cellulose generating a bismuth‐cellulose composite as paper sheets. Antibacterial evaluation indicates that the Bi‐cellulose materials have analogous or greater activity against Gram positive bacteria when compared with commercial silver based additives: silver sulfadiazine loaded at 0.43 wt % into nanocellulose produces a 10 mm zone of inhibition on the surface of agar plates containing S. aureus whereas [BiPh(OP(=O)Ph2 )2 ] loaded at 0.34 wt % produces an 18 mm zone of inhibition. These phenyl bis ‐phosphinato bismuth(III) complexes show potential to be applied in materials in healthcare facilities, to inhibit the growth of bacteria capable of causing serious disease. Abstract : Bismuth–nanocellulose composites utilise the powerful antibacterial activity of poorly soluble phenyl bismuth(III) phosphinates [BiPh(OP(=O)R1R2)2] in combating multi‐drug resistant bacteria (incl. VRE, MRSA) at Bi loading levels as low as 0.5 wt%.